The heat storage variability in the Brazil Current - Catherine B. Bou-Haya; Olga T. Sato (Ocean and Coastal Research)
We investigated the variability of the oceanic heat storage on the western boundary of the South Atlantic Ocean. We aimed to understand the specific contribution of the Brazil Current as it travels southwards. The heat storage is evaluated near three latitudes, namely at 15◦S, 24◦S and 34.5◦S. Numerical outputs of the oceanic potential temperature, salinity, and meridional components of the current’s velocity resulting from the Estimating the Circulation and Climate of the Ocean (ECCO) model were used. We examined the time series of the heat storage from 1992 to 2015 for the three latitudes. The mean heat storage increased towards the south with a maximum at 24◦S. At 34.5◦S, there is a decrease in this property possibly due to its proximity to the Brazil-Malvinas Confluence. The Brazil Current’s volume transport time series was correlated with the corresponding heat storage. The latitude that presented the highest correlation at interannual scale was 15◦S with a value of 0.84 at a 95% of confidence level. The model outputs were also compared with in situ expendable bathythermograph measurements. Despite the presence of gaps and peaks indicating extreme events in the in situ data, both time series were statistically close and they showed similar mean annual cycles. No significant long-term HS trend was found at any of the three latitudes.